Early fundus fluorescein angiographic findings and sequelae in traumatic retinopathy: case report. - Beckingsale, A B (1983)
A 44-year-old man involved in a minor road traffic accident developed traumatic retinopathy in both eyes. We present the unusual early angiographic findings and the late sequelae of persistent ring scotomata. The previous work on the retinal pathophysiology is reviewed, and we suggest that the total clinical picture in traumatic maculopathy may often be a combination of the 'angiopathic retinal trauma' of Purtscher and the 'commotio retinae' of Berlin, that is, a combination of haemodynamic forces leading to vascular damage in the nerve fibre layer and of direct mechanical forces leading to photoreceptor destruction.